2020
DOI: 10.3390/nano10061214
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Analysis Identifies Markers of Exposure to Cadmium Sulphide Quantum Dots (CdS QDs)

Abstract: The use of cadmium sulphide quantum dot (CdS QD)-enabled products has become increasingly widespread. The prospect of their release in the environment is raising concerns. Here we have used the yeast model Saccharomyces cerevisiae to determine the potential impact of CdS QD nanoparticles on living organisms. Proteomic analyses and cell viability assays performed after 9 h exposure revealed expression of proteins involved in oxidative stress and reduced lethality, respectively, whereas oxidative stress declined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 76 publications
0
11
0
Order By: Relevance
“…The figure was obtained by comparing 98 significant proteins obtained with 2D-PAGE with 88 selected proteins obtained with PF2D and the significant group of transcripts obtained with an Arabidopsis microarray platform. It is well known that the correlation between proteomics and transcriptomics is moderate to low [ 25 , 29 ], and in this case is also strongly biased by the difference between the higher number of transcripts and the lower number of proteins. Therefore, the proteins/transcripts considered as molecular markers showing this degree of correlation in the three comparisons are viewed as robust enough to be considered candidate “-omics” CdS QDs exposure markers.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The figure was obtained by comparing 98 significant proteins obtained with 2D-PAGE with 88 selected proteins obtained with PF2D and the significant group of transcripts obtained with an Arabidopsis microarray platform. It is well known that the correlation between proteomics and transcriptomics is moderate to low [ 25 , 29 ], and in this case is also strongly biased by the difference between the higher number of transcripts and the lower number of proteins. Therefore, the proteins/transcripts considered as molecular markers showing this degree of correlation in the three comparisons are viewed as robust enough to be considered candidate “-omics” CdS QDs exposure markers.…”
Section: Resultsmentioning
confidence: 99%
“…These two techniques use a different pH range (5–8 vs. 4–8.5), a different solubilization for proteins (SDS vs. urea), and a different quantity of proteins (4 mg vs. 400 µg); therefore, they are often seen as complementary [ 28 ]. However, other proteomic techniques, like iTRAQ, have been shown to give a greater number of identifications [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is evident that the treatment with CdS QDs determines the modulation, up or down, of proteins involved in oxidative phosphorylation as the ATP-dependent activity class listed in Figure 4 A. In fact, Gallo et al, (2020) [ 37 ] demonstrated that CdS QDs treatments caused a reduction in oxidative phosphorylation and in ATP production in yeast. Moreover, some proteins involved in the energy production, ATP synthase subunit alpha (Atp1) and ATP-dependent Clp protease ATP-binding (Clpt1), were down-regulated ( Figure 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is evident that the treatment with CdS QDs determines the modulation, up or down, of proteins involved in oxidative phosphorylation. In fact, Gallo et al, (2020) [32] demonstrated that CdS QDs treatments caused a reduction in oxidative phosphorylation and in ATP production in yeast. Moreover, some proteins, involved in the energy production, ATP synthase subunit alpha (Atp1) and ATP-dependent Clp protease ATP-binding (Clpt1), were down regulated (Figure 2).…”
Section: Proteomic Analysis Of Differentially Expressed Proteins In A...mentioning
confidence: 99%
“…This was already shown at phenotypic level [7], but it is confirmed here at protein level. The mechanism of hyperaccumulation certainly extend from ionic to nano metals, as well the mechanism of resistance [32]. But the mechanism of tolerance rests on different proteins and functions, not excluding those that lead to a biotransformation of the nano-form once inside the plant [34].…”
Section: Supplementary Materialsmentioning
confidence: 99%